P121 Choose to test. (8th June 2017) - Syred, Jonathan; Howroyd, Chris; Holdsworth, Gillian; Spelman, Kes; Baraitser, Paula
Abstract : Introduction: Choice is an increasingly important element of health care. We introduced choice of test into an online sexual health service. Methods: Users were offered testing based on their risk profile (table 1) with an option to request additional tests. Routinely collected anonymised data were collected on choice of test. Results: 2550 users ordered tests (30/10/16 – 19/12/16). 56% were <24, 10% were from black or ethnic minority (BME) groups and 17% were men who have sex with men (MSM). 1853 (72.6%) returned a test, 6.7% were positive for any STI. Of the non-BME/non-MSM users offered chlamydia/gonorrhoea testing, 66% chose to add HIV + syphillis testing. Of the BME/non-MSM users offered chlamydia/gonorrhoea + HIV testing, 71% chose to add syphilis testing. Of the MSM users offered chlamydia/gonorrhoea (genital, oral, anal) + HIV + syphilis testing, 85% chose this option. 6% chose to omit the HIV/syphilis test. User choice resulted in 611 fewer HIV tests, 596 fewer syphilis tests and 27 fewer chlamydia/gonorrhoea tests. Discussion: Online service users actively exercise choice in STI test selection. The majority of users choose to test for chlamydia, gonorrhoea, HIV and syphilis regardless of what they are offered. User choice of test reduces the total number of tests offered online.